Níveis de sódio e cloro para codornas italianas destinadas à produção de carne - Raquel, Débora Linhares (2009)
Two experiments were conducted to determine the best sodium and chlorine nutritional levels to Italian quails for meat production (aged 1 to 49 days). In each trial, 384 one-day quails were distributed in a completely randomized design with six treatments and eight replications of eight birds of experimental unit. The levels of sodium and chlorine evaluated were: 0,07; 0,12; 0,17; 0,22; 0,27 and 0,32%. It was observed a quadratic effect of the sodium levels on feed intake, weight gain and yields of carcass and thigh plus drumstick, with optimal levels of 0,257%, 0,216%, 0,207% and 0,191% respectively. The increase in sodium level in the diet produced a linear decrease in feed conversion and an in increase in water intake. However, the excreta moisture and breast yield were not significantly affected by the sodium levels. As for chlorine, we did not observe any significant effects of the chlorine levels in the diets on all the parameters evaluated. From the results, we can recommend that the diets for Italian quails bred for meat production, in the phase from 1 to 49 days, are formulated with 0,22% of sodium level and chlorine levels from 0,07% to 0,32%.